2015
DOI: 10.1016/j.ymgme.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid synaptic proteins as useful biomarkers in tyrosine hydroxylase deficiency

Abstract: Tyrosine hydroxylase (TH) deficiency is an inborn error of dopamine biosynthesis and a cause of early parkinsonism. Two clinical phenotypes have been described. Type "B": early onset severe encephalopathy; type "A": later onset, less severe and better response to L-dopa. We aimed to study the expression of several key dopaminergic and gabaergic synaptic proteins in the cerebrospinal fluid (CSF) of a series of patients with TH deficiency and their possible relation with the clinical phenotype and response to L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…[ 11 ] In addition, the CSF synaptic proteins dopamine transporter, D2-receptor and vesicular monoamine transporter are regarded as useful biomarkers for THD. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] In addition, the CSF synaptic proteins dopamine transporter, D2-receptor and vesicular monoamine transporter are regarded as useful biomarkers for THD. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of the DRD2 A1 allele, then, may have an interesting intrinsic -protective mechanism waiting for amino-acid introduction such as L-phenylalanine and L-tyrosine (rate-limiting substrates in the synthesis of dopamine). Moreover, Ortez et al [244] recently reported that in "tyrosine hydroxylase deficiency" the dopamine transporter (DAT) and vesicular monoamine transporter type 2 were up-regulated leading to a hypodopaminergic trait [244]. Kim et al [245] also showed that locomotor activity responses of these Dopamine-deficient (DA-/-) mice to dopamine D2 receptor agonists were 13-fold greater than the response elicited from wild-type mice [245].…”
Section: Why the Addictive Brain Favors Amino-acid Therapy [Nat™]mentioning
confidence: 99%
“…Around 70 cases have been reported so far starting not only in infancy but also in adolescence and adulthood. [3][4][5][6][7][8][9][10][11][12] Although different phenotypes have been described, two main forms can be outlined. Type A refers to a progressive hypokinetic-rigid syndrome (HRS) plus dystonia, with onset in infancy or childhood (►Table 1).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Dopaminergic receptors type 2 increase as L-DOPA doses and HVA concentration gradually raised in a B phenotype patient, whereas the opposite results were found in two patients with A phenotype. 12 Functional studies of TH missense variants have revealed specific kinetic anomalies and activities toward different substrates that may contribute to the development of individualized therapy for THD patients. 14…”
Section: Pathophysiology and Diagnosismentioning
confidence: 99%